Preparation and Characterization of Reduced Graphene Oxide Decorated With Iron Oxide Nanoparticles - Khalaf, Kamila Yassin (American Journal of Biomedicine and Pharmacy, 2025)
After being synthesized, graphene oxide was treated with potent reducing agents to decrease it. Nano iron oxide was then used to adorn the reduced graphene oxide sheets. The produced compounds were subjected to spectral and nanoscopic analyses using FT-IR, FESEM, AFM, and XRD.